The Concept of Nonviolence in Everyday Life of Students: a Focus Group Study - O. Yu. Kaplun; Shao Yupei (Высшее образование в России)
The purpose of this paper is to explore perceptions of theoretical foundations of nonviolence theory by modern students and their willingness to apply ideas of nonviolence to everyday life. The study problem lies in the fact that, in general, the scantily explored phenomenon of nonviolence is mostly studied in the context of philosophical and ethical understanding, ideology, and politics. While the values of nonviolence individual understanding, their local application in everyday life is still remain unexplored. Research design: focus group methodology. In this study, the focus group method was used as the main one for data collection, as it gives participants the opportunity to explore the topic in a focused discussion. Also, a phenomenological or «lived experience» approach was used since it would allow an exploration and understanding of the opinions of student. The focus group topic template included two parts, in the first part the participants discuss and interpret the ideas about the theoretical foundations of the concept of nonviolence, in the second part the focus group members share their own experiences and discussed the possibility of implementing the ideas of the nonviolence concepts in everyday life. The focus group discussions were audio-recorded and transcribed verbatim with the permission of the participants. When notes were summarized and analyzed, which allowed researchers to identify five key topics to draw conclusions about the place and role of violence and nonviolence in students’ daily lives. The article shows that the focus group participants mostly share the conceptual ideas of the nonviolence theories, but allow situations in which the use of force is necessary. The conclusions from this article can be used in further research aimed at studying the forms and strategies of conflict resolution in the daily life of youth.